Efeito do teor de ferro na síntese de vitrocerâmicos de basalto - Lima, Luiza Felippi de (My University, 2020)
Basalts, which cover about 70% of the Earth's surface, are igneous rocks originated from the cooling and solidification of magma on the Earth's surface. When the magma is cooled rapidly, it forms a glass. When cooled slowly, it crystallizes, totally or partially, forming several minerals. Products obtained from the melting of rocks have a wide market and can be considered the precursors of the glass ceramic technology. The glass-ceramic materials are ceramic materials, in which the crystalline phases are formed by controlled nucleation and crystallization of a base glass. These materials are promising due to the possibility of converting low-cost natural raw materials into products with excellent mechanical, thermal and chemical properties. Basalt glasses, when thermally treated, have the possibility of forming glass-ceramic materials if the Fe2O3/FeO ratio of the rock composition that originated it is greater than 0.5. In this work an FSG basalt was used to produce glass-ceramic materials by changing its chemical composition, by removing Fe2O3, by magnetic separation, and adding 5, 10 and 20% m. Fe2O3. To produce glassceramic the compositions were melted at 1500 °C for 1 h. A plateau of crystallization was applied at 950 °C for 3 h in the cooling step. Magnetic separation made it possible to reduce 13 %m. total Fe2O3 in the sample. Through the application of the petrurgical thermal treatment route, dendritic structures were obtained in the surface crystallization of the samples. With the increase of the iron content in the compositions there was an increase in the crystallization of the samples, observed by the thermal analysis, OM and SEM. It was concluded that all samples showed at least three different types of crystallization. On the surface, the predominant crystallization was dendritic, in the sample core the crystallization occurred in the form of small dots randomly distributed and, at the interface of the sample with the crucible, crystallization occurred heterogeneously, influenced by the chemical composition of the crucible. It was possible to verify the additive effect of the iron content in the crystallization of the glass-ceramic phases observed both in the amount and in the type of structure formed. The sample with reduced iron content was the only one that had a residual glass layer on the surface and did not show hematite in its structure. The samples show ed a Fe2O3/FeO ratio favorable to the formation of glass-ceramics, however it was observed that thetermination of this ratio is complex and the results were not conclusive. Thus, analyzes that evaluate the variation of the Fe2O3/FeO ratio throughout the entire heat treatment and not only the initial composition and the formed glass ceramic, could reveal its influence.
Os basaltos, que cobrem cerca de 70% da superfície do planeta Terra, são rochas ígneas originadas a partir do resfriamento e solidificação do magma na superfície terrestre. Quando o magma é resfriado rapidamente, forma um vidro. Quando resfriado lentamente, cristaliza, total ou parcialmente, formando diversos minerais. Os produtos obtidos a partir da fusão de rochas tem um amplo mercado e podem ser considerados os precursores da tecnologia dos vitrocerâmicos. Os materiais vitrocerâmicos são materiais cerâmicos, nos quais as fases cristalinas são formadas por nucleação e cristalização controladas de um vidro base. Esses materiais são promissores pela possibilidade da conversão de matérias-primas naturais, de baixo custo, em produtos com excelentes propriedades mecânicas, térmicas e químicas. Os vidros de basalto, quando tratados termicamente, têm a possibilidade de formar materiais vitrocerâmicos se a razão entre Fe2O3/FeO da composição da rocha que o originou for maior do que 0,5. Neste trabalho, um basalto da Formação Serra Geral foi utilizado para produzir materiais vitrocerâmicos mediante alteração da sua composição química, através da extração do Fe2O3, por separação magnética e adição de 5, 10 e 20 %m. de Fe2O3. Para a produção dos vitrocerâmicos, as composições foram fundidas a 1500 °C durante 1 h. Foi aplicado um patamar d cristalização a 950 °C por 3 h na etapa de resfriamento. A separação magnética possibilitou a redução de 13 %m. de Fe2O3 total da amostra. Mediante aplicação da rota de tratamento térmico petrúrgico, foram obtidas estruturas dendríticas na cristalização superficial das amostras. Com o aumento do teor de ferro nas composições, ocorreu o aumento na cristalização das amostras, observado por análise térmica, microscopia óptica e eletrônica. Concluiu-se que todas as amostras apresentaram pelo menos três tipos diferentes de cristalização. Na superfície a cristalização predominante foi dendrítica, no núcleo da amostra a cristalização ocorreu na fora de pequenos pontos distribuídos uniformemente e, na interface da amostra com o cadinho, a cristalização ocorreu de forma heterogênea, influenciada pela composição química do cadinho. Concluiu-se que a variação do teor de ferro altera tanto a quantidade, quanto o tipo de estrutura formada. A amostra com redução no teor de ferro foi a única que apresentou uma camada de vidro residual na superfície, e não apresentou formação de hematita na sua estrutura. As amostras apresentaram relação Fe2O3/FeO favorável à formação de vitrocerâmicos, entretanto foi observado que a determinação desta razão é complexa e os resultados não foram conclusivos. Dessa forma, análises que avaliem a variação da razão Fe2O3/FeO ao longo de todo tratamento térmico e, não somente da composição inicial e do vitrocerâmico formado, poderiam revelar qual a sua real influência.
Keywords: Basalto; Ferro; Vitrocerâmicos; Basalt; Iron; Glass-ceramics